TANGGUNG JAWAB NOTARIS TERHADAP PENYIMPANAN AKTA NOTARIIL SECARA ELEKTRONIK DITINJAU DALAM PERSPEKTIF PERUNDANG-UNDANGAN DI INDONESIA - Rizqi Akbar Kurniawan; Rosalinda Elsina Latumahina (Transparansi Hukum, 2025)
This study analyzes the legal responsibility of notaries in storing electronic notarial deeds with a focus on personal data protection. Notaries, as public officials, have a responsibility to maintain the confidentiality and security of entrusted documents, including deeds stored in electronic format. The legal perspective in Indonesia, especially after the enactment of Law No. 27 of 2022 concerning Personal Data Protection (UU PDP), presents new challenges to this obligation. The research method used is a normative legal approach, by reviewing the provisions of the PDP Law, the Notary Law (UUJN), and related regulations. The results of the study show that notaries are required to comply with the principles of personal data protection, such as transparency, accountability, and data security, as stipulated in the PDP Law. Violation of this obligation can have legal implications, including administrative, civil, and criminal sanctions. In addition, this study highlights the need to strengthen regulations for the technical implementation of electronic deed storage by notaries to ensure adequate data security standards. The conclusion of this paper recommends harmonization of the PDP Law and UUJN, as well as training for notaries to improve understanding of personal data security in the context of electronic document storage. Keyword: Notary, Notarial Deed, Personal Data Protection